COMAPRISON OF OUTCOMES IN LAPAROSCOPIC APPENDECTOMY VS OPEN APPENDECTOMY (Journal of Medical & Health Sciences Review, 2025)
Introduction: Acute appendicitis is a surgical emergency that is amongst the most frequently performed all over the globe, with open appendectomy being the conventional treatment. Laparoscopic appendectomy has become a popular practice in most centers with the introduction of the technique of minimally invasive surgery. Nevertheless, open appendectomy remains very common in low- and middle-income nations as a result of resource shortages.Objective: To compare the incidence of postoperative outcomes such as operative time, hospital stay, complications and pain scores between laparoscopic appendectomy and an open appendectomy.Material and Method: A prospective observational comparative study was carried out in Department of surgery, Jinnah Postgraduate Medical Center Karachi, Pakistan, from July 2024 to December 2024. One hundred patients (aged 18 years or older) having acute appendicitis were included (50 cases of laparoscopic appendectomy and 50 cases of open appendectomy). The information concerning demographic data, operative data, postoperative complications, pain measurements (VAS), and length of stay was collected and compared.Results: The mean age of patients was 28.4 ± 10.2 in the laparoscopic group and 30.7 ± 11.5 in the open group. The laparoscopic cases took a lot less time during the operation (45.3 +/- 9.6 minutes), as compared to Open surgery cases (60.1 ± 12.8 minutes). Laparoscopic patients had a shorter length of stay (2.1 ± 0.8 days) compared with those undergoing sharp appendectomy (3.2 ± 1.1 days). The incidences of postoperative wound infections were less in the laparoscopic (6%) than in the open group (18%).Conclusion: Laparoscopic appendectomy is more effective than open appendectomy due to decreased operating time, less operative morbidity, fewer complications, shorter stay and less postoperative pain. It should be promoted as the method of choice in surgery to be performed in tertiary care facilities in Pakistan, and work should be put into increasing the availability of laparoscopic facilities.